The Effects of the Government's Covid-19 Related Response on Migrant Women Living in Cape Town: Assessing the Coloniality of Citizenship in Post-Apartheid South African and the Potential for a New Citizenship Paradigm - Burton, Olivia (Department of Sociology, 2025)
In South Africa, the existing system continues to preserve unequal gendered citizenship rights based on colonial and apartheid hierarchies. Despite a rights based legal platform, the state reproduces racism, xenophobia and patriarchy, creating a multitude of vulnerabilities for black migrant women due to their triple discrimination. The Covid-19 pandemic and related restrictions have deepened global inequality, exacerbating the vulnerabilities experienced by the most marginalised people in society, both highlighting and reinforcing discrimination according to race, gender, class and nationality. This has been seen in governments' pandemic responses around the world, which have prioritised exclusion over solidarity. South Africa is a prime example of how the government's response has worsened the exclusion and violence to which these marginalised groups are exposed. Through qualitative interviews with migrant women living in Cape Town using an intersectional and feminist approach, this research evaluated the effects of the South African government's response to Covid-19, uncovering how it has exacerbated preexisting structural inequality and violence, increasing the vulnerabilities faced by migrant women living in Cape Town. Despite this pronounced precarity as a result of the response, the findings revealed how such experiences of vulnerability were nothing new to the participants. Rather, their experiences of exclusion constitute continuity of the existing system. Through this investigation, this research has revealed how the experiences of migrant women are symptomatic of the enduring coloniality of citizenship in South Africa, which has institutionalised their exclusion from citizenship.